THE USE OF MTS (MULTIPLE TIP SIZE) PROBE PERMEAMETER METHOD IN CARBONATE ROCK - Septi Anggraeni (Scientific Contributions Oil and Gas, 1999)
The fundamental control in petrophysical properties of carbonate rock can be quite different from sandstone, there-fore it needs different technique in permeability assessment. In this study we proposed a technique to assess permeability using probe permeameter for carbonate rock.The technique applied Multiple Tip Size (MTS) Probe permeameter which provides speedy, non destructively sampling at a significantly increased density. The key feature of the MTS is the use of different tip size. By using the MTS probe permeameter, the data can be screened to assess the appropriate data